Selected Papers from 2017 International Conference on Micro/Nanomachines - Jianguo Guan (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The 2017 International Conference on Micro/Nanomachines (http://www.icmnm.org/) was held in Wuhan, China, 25-28 August, 2017. Micro/nanomotors (MNMs), which are defined as micro/nanodevices capable of converting energy into autonomous motion, can be used to pick up, transport, and release various cargoes within a liquid medium. They have important potential applications, for example, in drug delivery, biosensors, protein and cell separation, microsurgeries, and environment remediation. MNMs can be classified into two categories, according to their propulsion mechanism. In this respect, self-propelled MNMs are capable of moving autonomously without external intervention, but they either require toxic fuel or have a short lifespan. MNMs actuated by external fields, such as light, magnetic field, and acoustic waves, are not subject to these problems, do not require toxic fuels, nor give rise to by-products during the motion process. For both self-propelled and field-actuated MNMs, there is still a long way to go before we reach practical applications. The future development of MNMs should be focused on improving the energy conversion efficiency through structure optimization, exploring new propulsion mechanisms and endowing MNMs with environmental responses for self-navigation, detection, and specific operations. In this way, MNMs will approach their practical application in biomedicine, environment treatment, microengineering, etc.